2007
DOI: 10.1063/1.2825004
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the turbulent decay of an afterspark channel with residual current

Abstract: This paper presents the results of an experimental study of a pulse discharge in air at atmospheric pressure and the post-discharge channel decay. It is shown for the first time that a relatively small residual current suppresses the development of gas-dynamic instability and stabilizes the channel. The results of the experiments are compared with predictions of our previously developed theoretical model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The authors observed that the hot gas produced by a single spark propagated over a few millimeters within tens of microseconds. In further developments, Leonov et al [26] investigated high current (~1.5 kA) sparks of 50-ns duration across long interelectrode gaps (50-60 mm) in air, and observed the onset of strong turbulence attributed to Rayleigh-Taylor instabilities, with a radial expansion of the hot gas core to distances up to 50 times the radius of the initial spark channel. More recently, this effect was also observed in nanosecond sparks with lower current (~100 A) [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the hot gas produced by a single spark propagated over a few millimeters within tens of microseconds. In further developments, Leonov et al [26] investigated high current (~1.5 kA) sparks of 50-ns duration across long interelectrode gaps (50-60 mm) in air, and observed the onset of strong turbulence attributed to Rayleigh-Taylor instabilities, with a radial expansion of the hot gas core to distances up to 50 times the radius of the initial spark channel. More recently, this effect was also observed in nanosecond sparks with lower current (~100 A) [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It means that the global hydrodynamic flux is still directed towards the outside of the channel at this time, driven by the continuous energy deposition from the Joule heating in the plasma. As long as this heating remains sufficient to displace neutrals outside of the discharge channel, hydrodynamic instabilities at the boundary are prevented from forming 40 . The discharge is therefore inherently stable.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the experimental data shows that the size of the perturbed region is several times larger than it has to be appeared if only conventional laminar or turbulent diffusion mechanisms were at play. Comparison of the measured channel radius and the channel radius calculated using the conventional model, 14,19,22 which does not account for jet formation, is shown in Fig. 6͑a͒.…”
Section: B Initial Afterspark Expansionmentioning
confidence: 98%